Prioritizing international agricultural research investments: lessons from a global multi-crop assessment - Pemsl, Diemuth E.; Staver, Charles; Hareau, G.; Alene, A.; Abdoulaye, Tahirou; Kleinwechter, U.; Labarta, Ricardo Antonio; Thiele, Graham (Elsevier, 2022)
Investments in international agricultural research have proven very successful at an aggregated level over the past decades. Decision makers, however, face the tough question of how best to allocate limited public funds across increasingly diverse research areas to achieve the largest impacts. Simultaneously, donors demand more accountability from research institutions with regards to use of funds and resulting impacts on food and nutrition security, the environment, gender equality and poverty reduction. From 2012-2014, the CGIAR Research Program on Roots, Tubers and Bananas (RTB) undertook a systematic, quantitative ex-ante priority assessment across five key crops to inform its strategic research portfolio decisions. In-depth studies were conducted for cassava, banana, potato, sweetpotato, and yams with a harmonized methodological framework. The assessments comprised: 1) elicitation of major production constraints and research opportunities through global expert surveys; 2) identification of priority research interventions; 3) ex ante estimation of costs and benefits for two adoption scenarios using partial equilibrium economic surplus models; and 4) poverty impact simulations. Results suggest substantial, although variable benefits for all assessed potential research investments and provide a range of impact indicators (adoption area, number of beneficiaries, net present value, internal rate of return, and poverty reduction). The findings have since informed the research portfolio development of RTB and were critical for continued program funding in the second phase. This paper presents the methodology and results and then focuses on the policy implications and lessons learned to strengthen future priority assessments in agricultural research.